Long term experience with growth hormone treatment in children with chronic renal failure - Schaefer, Franz; Haffner, Dieter; Wühl, Elke; Mehls, Otto (Peritoneal dialysis international, 1999)
After a decade of experience with recombinant human growth hormone (rhGH) in children with chronic renal failure (CRF), the long-term efficacy and safety of the drug is now established. In prepubertal children, partial catch-up growth is achieved during the first three treatment years, followed by sustained percentile-parallel growth. Discontinuation of rhGH treatment results in catch-down growth in 75% of patients. Treatment efficacy is inversely correlated with age and baseline height velocity, and positively influenced by genetic target height and residual renal function. Skeletal maturation is not accelerated, suggesting a true increase in final height potential. Side effects are limited to a stimulation of insulin secretion, which is not associated with changes in glucose tolerance, and occasional cases of benign intracranial hypertension., In summary, the advent of rhGH has opened a new era in the management of growth failure in CRF. Available evidence suggests that treatment should start in early childhood and early in the course of renal failure, and should be continued at least until renal transplantation. It remains to be seen whether the beneficial effect of rhGH on height observed during the prepubertal period will result in an eventual increase in adult height.
Gesehen am 18.01.2021